Miracle Stories in Motion—On the Three Editions of Guangshiyin Yingyanji - Lai, Chon Iat (Religions, 2023)
Previous studies have assumed that the purpose of Yingyanji was to produce texts that are proselytistic or evangelical. Through the analysis of Guangshiyin Yingyanji, we find that lay people have created Yingyanji for a long time. Its main purpose was not to spread religion, but to record regional memories and family beliefs, which were mainly circulated among friends and relatives. Moreover, the miracle stories contained in Guangshiyin Yingyanji often have different versions within the three systems of Zhiguai, Yingyan, and Gantong. Through an analysis of these different versions, we can better grasp the purpose of rewriting texts under different systems, and the struggle for ideas which they embody.